Hsa_circ_0001879 promotes the progression of atherosclerosis by regulating the proliferation and migration of oxidation of low density lipoprotein (ox-LDL)-induced vascular endothelial cells via the miR-6873-5p-HDAC9 axis. Issue 2 (20th December 2021) - Li, Feifei; Chen, Yahui; He, Zhiling; Wang, Chuangchang; Wang, Xiaoli; Pan, Guangming; Peng, Jiang yang; Chen, Qiuxiong; Wang, Xia
ABSTRACT: Atherosclerosis (AS) is a typical vascular disease. Emerging evidence has shown that circRNAs play key roles in the progression of AS, but the potential function and underlying mechanism of hsa_circ_0001879 remains unknown. We detected the expression level of hsa_circ_0001879 was determined by qRT-PCR, and the proliferation rate and migration ability of HUVECs were measured by CCK-8 assay and Transwell assay, respectively. Proliferative markers and epithelium mesenchymal transition (EMT) markers were measured through immunoblotting. A dual luciferase activity assay was performed to detect the interaction between circRNAs, miRNAs, and mRNAs. Hsa_circ_0001879 was upregulated in AS patients. Hsa_circ_0001879 inhibited the proliferation and migration ability of Human umbilical vein endothelial cells (HUVECs). Hsa_circ_0001879 directly bound to miR-6873-5p and acted as a sponge. miR-6873-5p-induced HDAC9 mRNA degradation was inhibited by hsa_circ_0001879. Hsa_circ_0001879 decreased the proliferation and migration of HUVECs by inhibiting miR-6873-5p-induced HDAC9 degradation.